Man meets frog : perceptions, use and conservation of amphibians by indigenous people - Das, Indraneil (Oxford University Press, 2012)
Describes humans’ exploitation of amphibians for food, and the role of amphibians as part of myths, beliefs, and folklore. There are long tables of species and beliefs for various peoples around the world.